Menopause and behavioral effects: How to proceed? Literature review (Research, Society and Development, 2023)
Through the context of women's reproductive health, a change in the fertile cycle is identified as a result of hormonal decline and the aging process caused by menopause. In this sense, in view of the hormonal and psychological changes that this phase of menopause causes in women, the present study aims to study the behavioral variations of women and how to proceed in the face of the phase in which the menopause period comprises. This is an integrative literature review study. For this purpose, the following databases were used: Pubmed, Scielo, Lilacs and Portal da Ebsco. The keywords used in the Health Descriptors (Decs) to extract the information were the following Decs: “Climate and Menopause”, “Menopause and behavioral changes” and “Menopause and Herbal Medicines”. Complete articles were included, covering Portuguese and English languages, as well as articles referring to the last five years, generating a quantitative of 124 studies. Considering the exclusion criteria as articles that were inconclusive or that did not have relevant findings for the research, 28 articles that fit the purpose of the study were selected. Menopause is the result of the loss of ovarian function, due to a hormonal fall, being recognized after the permanent cessation of menstruation, a period corresponding to 12 months of amenorrhea. The findings show that a humanized and comprehensive care for women must take into account their uniqueness, in addition, qualified listening by the multidisciplinary team at this stage is essential for possible interventions and appropriate treatment.